Increase in national intravenous thrombolysis rates for ischaemic stroke between 2005 and 2012: is bigger better?. Issue 1 (December 2016) - Scherf, S.; Limburg, M.; Wimmers, R.; Middelkoop, I.; Lingsma, H.
Abstract Background Intravenous thrombolytic therapy after ischaemic stroke significantly reduces mortality and morbidity. Actual thrombolysis rates are disappointingly low in many western countries. It has been suggested that higher patient volume is related to shorter door-to-needle-time (DNT) and increased thrombolysis rates. We address a twofold research question: a) What are trends in national thrombolysis rates and door-to-needle times in the Netherlands between 2005–2012? and b) Is there a relationship between stroke patient volume per hospital, thrombolysis rates and DNT? Methods We used data from the Stroke Knowledge Network Netherlands dataset. Information on volume, intravenous thrombolysis rates, and admission characteristics per hospital is acquired through yearly surveys, in up to 65 hospitals between January 2005 and December 2012. We used linear regression to determine a possible relationship between hospital stroke admission volume, hospital thrombolysis rates and mean hospital DNT, adjusted for patient characteristics. Results Information on 121.887 stroke admissions was available, ranging from 7.393 admissions in 2005 to 24.067 admissions in 2012. Mean national thrombolysis rate increased from 6.4 % in 2005 to 14.6 % in 2012. Patient characteristics (mean age, gender, type of stroke) remained stable. Mean DNT decreased from 72.7 min in 2005 to 41.4 min in 2012. Volume of stroke admissions was not an independent predictor for mean thrombolysis rate nor for mean DNT. Conclusion Intravenous thrombolysis rates in the Netherlands more than doubled between 2005 and 2012, in parallel with a large decline in mean DNT. We found no convincing evidence for a relationship between stroke patient volume per hospital and thrombolysis rate or DNT.